The Association Between Intergenerational Trauma, Perceived Social Support and Post Traumatic Growth among Young Adults - Ishika Kalra; Rita Kumar (International Journal of Children, 2025)
This study explores the intricate relationship between intergenerational trauma, perceived social support, and post-traumatic growth (PTG) among young adults in the Indian subcontinent. Drawing on a sample of 199 participants, the research examines how adverse childhood experiences (ACE) transmitted across generations impact individuals' psychological well-being and their capacity for growth. In particular, the study looks into how perceived social support from friends, family, and other people can help to moderate PTG. Despite expectations, the results indicate weak correlations between intergenerational trauma and both perceived social support and PTG. The findings challenge the notion that childhood adversity directly fosters personal growth, emphasizing the need for more nuanced explorations into the factors that mediate trauma recovery, such as coping strategies and resilience. The study also emphasizes the importance of cultural context, especially in collectivist societies where people's recovery paths are shaped by the interaction of social norms, shared trauma histories, and familial expectations. The weak associations found indicate that outcomes are significantly shaped by variables other than direct trauma experiences, such as the caliber and accessibility of social support. This study emphasizes how crucial it is to create culturally aware treatment approaches that take into consideration the intricate relationships between trauma transmission, social support networks, and personal development. This study offers important insights for future research and clinical practice by concentrating on the Indian subcontinent, which advances our understanding of how collectivist cultural frameworks affect the transmission of trauma over generations and the possibility of psychological development.
Keywords: Indian subcontinent; Intergenerational trauma; post-traumatic growth; resilience; social support; young adults